National Practitioner Data Bank malpractice payment reports related to surgical never events: 1991–2025 nationwide trends - Tucker Bettis; Quynh Tran; Logan Glosser; Felipe Maegawa; Snehal Patel (Patient Safety in Surgery, 2026)
Abstract Background Retained surgical items and wrong site, wrong patient, and wrong procedure events are commonly termed surgical “never events,” although many patient safety experts now prefer a more neutral and precise definition such as, largely preventable events (SLPEs). National Practitioner Data Bank (NPDB) allegation codes approximate these categories, but national trends in malpractice payments involving these events remain poorly characterized, and the suitability of the NPDB for this purpose has not been formally examined. Methods We retrospectively analyzed physician medical malpractice payment reports in the February 2026 NPDB Public Use Data File. Reports containing allegation code 322, 330, 333, or 334 in either allegation position were analyzed separately and as a pooled cohort. Payments were adjusted to 2025 dollars. Annual counts and the proportion of eligible physician reports containing a qualifying code were modeled from 2004 to 2025. Severity, age, sex, and setting were examined among reports from 2004 onward. Sensitivity analyses were restricted to the NPDB Surgery Related allegation group. Results The pooled cohort included 15,196 reports: 7,646 with code 322, 3,499 with code 330, 93 with code 333, and 3,983 with code 334. From 2004 to 2025, pooled annual counts decreased by an average of 4.1% per year (count ratio, 0.959; 95% CI, 0.952–0.965). Counts decreased in the three larger categories; estimates for code 333 were imprecise. The proportion of eligible physician reports containing any qualifying code decreased from 3.98% to 3.05% (annual odds ratio, 0.984; 95% CI, 0.980–0.988). The pooled median payment was $75,220 (IQR, $28,847–$215,003). Code 334 had the highest median payment ($168,723). Death was listed in 442 reports from 2004 onward (6.1%), and the median interval from the act or omission to the report was three years. Conclusions Reports containing these allegation codes decreased across all categories from 2004 to 2025. Their proportion among eligible physician reports also decreased, suggesting that the trend was not attributable solely to declining overall report volume. These findings describe paid malpractice reports and should not be interpreted as estimates of never event incidence. The analysis also delineates the structural limits of the NPDB for surgical safety research and identifies specific, confidentiality preserving enhancements that would increase the research value of the Public Use Data File.